2017
DOI: 10.1097/mnm.0000000000000681
|View full text |Cite
|
Sign up to set email alerts
|

UK audit of quantitative thyroid uptake imaging

Abstract: A UK-wide audit showed that thyroid uptake imaging is still a common test in the UK. It was found that most centres do not adhere to all aspects of the BNMS practice guidelines but that quantitative results are reasonably consistent for Tc-based scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
2
4
0
Order By: Relevance
“…Our survey among nuclear medicine departments at Dutch hospitals, despite moderate response in a fairly small sample size, clearly showed significant differences in technical performance of RAIU test examinations in routine clinical practice, including differences in equipment, isotope, isotope formulation, amount of activity, use of neck phantoms, frequency and duration of reference measurements, distance to collimator head, background measurements and region-of-interest delineation. These results are in line with previous studies from the UK [ 20 ], France [ 21 ] and Germany [ 22 ]. The study from the UK was a national audit of thyroid uptake imaging that showed large variation in software, isotope, dosages, collimators, duration and ROI delineation and concluded that most UK centers do not adhere to all aspects of BNMS guidelines [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our survey among nuclear medicine departments at Dutch hospitals, despite moderate response in a fairly small sample size, clearly showed significant differences in technical performance of RAIU test examinations in routine clinical practice, including differences in equipment, isotope, isotope formulation, amount of activity, use of neck phantoms, frequency and duration of reference measurements, distance to collimator head, background measurements and region-of-interest delineation. These results are in line with previous studies from the UK [ 20 ], France [ 21 ] and Germany [ 22 ]. The study from the UK was a national audit of thyroid uptake imaging that showed large variation in software, isotope, dosages, collimators, duration and ROI delineation and concluded that most UK centers do not adhere to all aspects of BNMS guidelines [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous studies from the UK [ 20 ], France [ 21 ] and Germany [ 22 ]. The study from the UK was a national audit of thyroid uptake imaging that showed large variation in software, isotope, dosages, collimators, duration and ROI delineation and concluded that most UK centers do not adhere to all aspects of BNMS guidelines [ 20 ]. The study from France was a nationwide survey that also showed significant variation in isotope, dosages, time points of measurement post-injection and method of thyroid volumetry (ultrasound, scintigraphy or palpation) [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Geographical location-based reference range for thyroid uptake of 99mTc pertechnetate are rarely found in literature and the normal reference values for thyroid uptake of 99mTc pertechnetate changes significantly from time to time 6,7 . 99mTc for thyroid uptake is now commonly used in several countries but fluctuations in the normal reference values of 99mTc thyroid uptake has been documented at different centers 8 . The normal value for 99mTc uptake recommended globally is 0.3-4.5% 9 .…”
Section: Discussionmentioning
confidence: 99%